First observation of the decay D0 → K-π+[my]+[my]- in the [rho]0-[omega] region of the dimuon mass spectrum - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Gerick, David; Gersabeck, Evelina; Grillo, Lucia; Han, Xiaoxue; et al. (Physics letters, 2016)
A study of the decay D0→K−π+μ+μ− is performed using data collected by the LHCb detector in proton-proton collisions at a centre-of-mass energy of 8 TeV, corresponding to an integrated luminosity of 2.0 fb−1. Decay candidates with muon pairs that have an invariant mass in the range 675-875 MeV/c2 are considered. This region is dominated by the ρ0 and ω resonances. The branching fraction in this range is measured to beB(D0→K−π+μ+μ−)=(4.17±0.12(stat)±0.40(syst))×10−6. This is the first observation of the decay D0→K−π+μ+μ−. Its branching fraction is consistent with the value expected in the Standard Model.